Forecast of Organic Diversification of Agriculture in a Global Perspective - GRIGORUK, Vladimir V.; AKIMBEKOVA, Chulpan U.; UMBITALIEV, Altynsary D. (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021, 2021)
The achievements of organic farming in the world and in the leading countries of the organic movement are very successful. In Kazakhstan, organic farming also has positive results, but the scale of its development does not match the country's capabilities. The purpose of this research is to study the suitability of agricultural land for organic farming and to substantiate the forecast of its organic diversification in a global perspective. The basis for calculations on the involvement of used lands and development of new lands in organic circulation is an eco-systematic assessment of landscapes by their level of favorableness for agriculture, an eco-toxicological assessment of anthropogenic soil pollution as a result of agricultural and other activities, as well as an assessment of agricultural lands by their reclamation state (uncomplicated by negative signs, filled with rubble, saline, deflated, etc.). The global forecast was made by the expert and logical method on the example of the Almaty region of Kazakhstan for a 50-year perspective (until 2070) in three scenarios: pragmatic, optimal and real. According to calculations, at the end of the given perspective, it is possible to increase the share of organic cultivated land and the production of organic products in the aggregate indicators of the cultivated land, according to the scenarios, to 39, 28 and 23% and increase the volume of production by 3.2; 2.9 and 2.7 times.